Black pleural effusion: an unusual complication of pseudocyst pancreas - Jagannath, Spandana; Kumar, Ashok (International Surgery Journal, 2021)
Pleural effusion following rupture of pancreatic pseudocyst into the pleural cavity resulting into pancreaticopleural fistula is an extremely uncommon complication of acute pancreatitis. Pancreaticopleural fistula also results from disruption of a major pancreatic duct usually due to an underlying pancreatic disease (chronic pancreatitis), trauma, or iatrogenic injury. Pleural effusion is predominantly left sided; however, right-sided and bilateral effusion occurs in 19% and 14% of patients respectively. The pleural effusate can be either serous, serosanguinous or black in colour. Analysis of pleural fluid for raised amylase will confirm the diagnosis and investigations like computed tomography (CT), endoscopic retrograde cholangiopancreatography (ECRP) or magnetic resonance cholangiopancreatography (MRCP) may establish the fistulous communication between the pancreas, pseudocyst and pleural cavity. The optimal treatment strategy has traditionally been medical management with thoracocentesis and/or tube thoracostomy and exocrine suppression with octreotide and ERCP stenting of the fistulous pancreatic duct. Surgery, in the current era, is considered in the event patient fails to respond to conservative management or the patient’s condition deteriorates. We report the case of a 24-years-old gentleman who was diagnosed with chronic idiopathic pancreatitis with pseudocyst who developed right sided black pleural effusion.